A combined theoretical and experimental investigation of uranium dioxide under high static pressure. (8th June 2015) - Crowhurst, J C; Jeffries, J R; Åberg, D; Zaug, J M; Dai, Z R; Siekhaus, W J; Teslich, N E; Holliday, K S; Knight, K B; Nelson, A J; Hutcheon, I D
Abstract: We have investigated the behavior of uranium dioxide (UO2 ) under high static pressure using a combination of experimental and theoretical techniques. We have made Raman spectroscopic measurements up to 87 GPa, electrical transport measurements up to 50 GPa from 10 K to room temperature, and optical transmission measurements up to 28 GPa. We have also carried out theoretical calculations within the GGA +  U framework. We find that Raman frequencies match to a large extent, theoretical predictions for the cotunnite ( Pnma ) structure above 30 GPa, but at higher pressures some behavior is not captured theoretically. The Raman measurements also imply that the low-pressure fluorite phase coexists with the cotunnite phase up to high pressures, consistent with earlier reports. Electrical transport measurements show that the resistivity decreases by more than six orders of magnitude with increasing pressure up to 50 GPa but that the material never adopts archetypal metallic behavior. Optical transmission spectra show that while UO2 becomes increasingly opaque with increasing pressure, a likely direct optical band gap of more than 1 eV exists up to at least 28 GPa. Together with the electrical transport measurements, we conclude that the high pressure electrical conductivity of UO2 is mediated by variable-range hopping.